Unlocking Excellence: The Impact of Parental Involvement on Quality Education in Addis Ababa's Private Schools - Dr. Easaw Alemayehu Assefa (The Journal of Quality in Education)
Purpose: This study aims to investigate the impact of parental engagement on the quality of education in private schools, emphasizing how various involvement dimensions contribute to educational outcomes.